The Influence of Tenure of Service Rewards, Job Satisfaction, and Work Environment on the Performance of Regional Inspectorate Employees in Kolaka Regency, Southeast Sulawesi Province - Acep Kristanto; Nurdin Latif; Yusram Adi (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2023)
The purpose of this study was to determine and analyze the effect of long service rewards, job satisfaction, and work environment on the performance of the employees of the Regional Inspectorate of Kolaka Regency, Southeast Sulawesi Province. In this study, the design used was a descriptive design that also examined the relationship between variables (causal design), which is useful to measure the relationship between research variables or to analyze the influence of a variable on other variables. In this study, data were collected ex post facto; in other words, the researcher relied on the respondents' perceptions to explain their experiences and then analyzed them according to a descriptive and causal design. The data collection technique in this study used the survey method, using a closed questionnaire as a tool. The sample for this research involved all employees—as many as 63 people. The results of the study show that long service awards, job satisfaction, and work environment will affect employee performance at the Regional Inspectorate, Kolaka Regency.